2015
DOI: 10.1002/ece3.1569
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting demographic history and gene flow patterns of two mangrove species on either side of theCentralAmericanIsthmus

Abstract: Comparative phylogeography offers a unique opportunity to understand the interplay between past environmental events and life-history traits on diversification of unrelated but co-distributed species. Here, we examined the effects of the quaternary climate fluctuations and palaeomarine currents and present-day marine currents on the extant patterns of genetic diversity in the two most conspicuous mangrove species of the Neotropics. The black (Avicennia germinans, Avicenniaceae) and the red (Rhizophora mangle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 89 publications
(148 reference statements)
4
38
0
Order By: Relevance
“…For example, the most distinctive genetic break in the AEP region divides mangrove populations into the Atlantic and Pacific Oceans. This was observed in all studied mangrove species in the AEP and is attributed to vicariance following the final closure of the Central American Isthmus [2,3]. Similarly in the IWP, the Malay Peninsula, which separates the East Indian Ocean (EIO) and South China Sea (SCS), was found to be a strong genetic barrier for many mangrove species.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…For example, the most distinctive genetic break in the AEP region divides mangrove populations into the Atlantic and Pacific Oceans. This was observed in all studied mangrove species in the AEP and is attributed to vicariance following the final closure of the Central American Isthmus [2,3]. Similarly in the IWP, the Malay Peninsula, which separates the East Indian Ocean (EIO) and South China Sea (SCS), was found to be a strong genetic barrier for many mangrove species.…”
Section: Introductionmentioning
confidence: 76%
“…Major mangrove plant lineages were separated into the Atlantic East Pacific (AEP) and the Indo-West Pacific (IWP) regions after the closure of the Tethys Sea, and subsequently evolved in independent trajectories, resulting in different species assembly in each region [1]. The striking similarities in genetic patterns across species within each region indicated that vicariance events, Quaternary climatic oscillation and oceanic currents may have a universal effect on the geographic distribution of genetic variation [2]. For example, the most distinctive genetic break in the AEP region divides mangrove populations into the Atlantic and Pacific Oceans.…”
Section: Introductionmentioning
confidence: 99%
“…Such post‐glacial recolonization resulted in genetic signatures that vary among taxa due to life history differences, local geography (Hewitt, ), and tolerance to the environmental conditions in the colonized areas (Davis & Shaw, ). Classic comparative phylogeographical studies address such differences by surveying patterns among co‐distributed taxa, although they often struggle to disentangle individual drivers of population structure (Carstens, Brunsfeld, Demboski, Good, & Sullivan, ; Carstens & Richards, ; Cerón‐Souza et al., ; Fouquet et al., ; Guo, Guo, et al., ; Maliouchenko, Palmé, Buonamici, Vendramin, & Lascoux, ; Marske, Leschen, & Buckley, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, their subtropical location increases the likelihood that glacial populations still exist, in contrast to temperate or boreal taxa (Castellanos‐Morales, Gámez, Castillo‐Gámez, & Eguiarte, ; Roberts & Hamann, ; Scheinvar, Gámez, Castellanos‐Morales, Aguirre‐Planter, & Eguiarte, ). Moreover, they have been likely separated since the closure of the CAI (Cerón‐Souza et al., , ; Dodd, Afzal‐Rafii, Kashani, & Budrick, ; Nettel & Dodd, ) which decreases the likelihood that secondary contact will affect the results (but see Takayama et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the remarkable differences in life-history traits of mangrove species, which should have had a strong influence on seed dispersal capability and, thus, population connectivity, it is plausible that not only vicariant events, but also climate fluctuations and marine currents would have contributed to distribution of genetic diversity (Cerón-Souza et al, 2015). Although adaptation to different habitats govern local distributional patterns, Duke (1995) also suggests that it is likely that the combination of dispersal and historical perturbations has a predominant role in determining the overall distribution patterns (Duke, 1995).…”
Section: Sri Lankan Mangroves In the Global Mangrove Landscapementioning
confidence: 99%